A scoping review : factors associated with musculoskeletal disorder in Bank Employees - Putri, Saskia Biyakto; Agushybana, Farid; Widjanarko, Bagoes (Science Midwifery, 2024)
Musculoskeletal Disorders (MSD) are a common issue among bank employees that can significantly impact their health and productivity. This research adopts a scoping review methodology, focusing on international journals related to the Analysis of Factors Associated with Bank Employees' Musculoskeletal Disorders (MSDs). Data from various studies reveal that the body areas most frequently affected by MSDs in the banking sector are the neck, lower back, and shoulders. Factors such as non-ergonomic working postures, improper computer usage, job-related stress, repetitive tasks, and insufficient breaks play pivotal roles in elevating the risk of MSDs. In efforts to mitigate these risks, the implementation of ergonomic training stress management, as well as a proactive prevention and regular monitoring approach within the banking work environment, becomes imperative. These findings offer insights into the elevated risk of MSDs in bank workers, providing a foundation for initiatives to enhance their well-being and work quality.